Cotton - Sneyd, Adam, 1978- (Cambridge MA Polity Press, 2016)
Spinning a fibrous tale -- The world cotton (dis)order -- Cotton on the land -- Cotton for the country -- Cotton in company hands -- Beyond the dirty white stuff -- Afterword: a learner in the world cotton order notes
Include Notes and Index